Autistic Traits Predict Social-Contact Uncertainty in University Students - Bertrams, Alex; Zäch, Myriam (Frontiers in Psychiatry, 2021)
Social anxiety (alternatively: social-contact uncertainty) in the university context can lead to reduced health, well-being, and performance, and can even cause premature leaving of education. With the present study, we intended to supplement cross-sectional studies on students’ autistic traits and social anxiety with longitudinal findings. We measured autistic traits and social-contact uncertainty of 118 university students on two occasions, roughly one year apart. Correlation, multiple regression, and cross-lagged analyses showed that more pronounced autistic traits predicted higher future social-contact uncertainty. Social-contact uncertainty did not predict autistic traits. We conclude that university students who are high in autistic traits tend not only to be more socially anxious at the moment but have a heightened risk of still being so in the future.